Repeatability of Perimacular Ganglion Cell Complex Analysis with Spectral-Domain Optical Coherence Tomography - Dorothy S. K. Ng; Preeti Gupta; Yih Chung Tham; Chye Fong Peck; Tien Yin Wong; Mohammad Kamran Ikram; Carol Y. Cheung (Journal of Ophthalmology)
Purpose. To assess the repeatability of spectral-domain optical coherence tomography to measure macular and perimacular ganglion cell complex thicknesses and compare retinal ganglion cell parameters between algorithms. Methods. Ninety-two nonglaucomatous eyes from 92 participants underwent macular and perimacular ganglion cell complex thickness measurement using OCT-HS100 Glaucoma 3D algorithm and these measurements were repeated for 34 subjects. All subjects also had macular ganglion cell-inner plexiform layer thickness measured by Cirrus HD-OCT Ganglion Cell Analysis algorithm. Intraclass correlation coefficient and Pearson’s correlation analyses were performed. Results. Subfields of both macular and perimacular ganglion cell complex thicknesses had high intraclass correlation coefficient values between 0.979 (95% confidence interval [CI]: 0.958–0.989) and 0.981 (95% CI: 0.963, 0.991) and between 0.70 (95% CI: 0.481–0.838) and 0.987 (95% CI: 0.956–0.989), respectively. The overall average ganglion cell complex and macular average ganglion cell-inner plexiform layer thicknesses were strongly correlated (r=0.83, P<0.001).  Conclusions. The assessment of macular and perimacular retinal ganglion cell parameters by OCT-HS100 Glaucoma 3D algorithm is highly repeatable, and strongly correlates to retinal ganglion cell parameters assessed by Ganglion Cell Analysis algorithm. A comprehensive evaluation of retinal ganglion cells may be possible with OCT-HS100.